STUDENTS' DIGITAL LITERACY COMPETENCIES IN INDONESIAN LANGUAGE SUBJECTS - Andi Sutisno; Ahmad, Dhika FS (Cirebon International Conference on Education and Economics Proceeding, 2024)
This study aims to describe the level of digital literacy competence of students in students in grades X and XI of SMKS NU Tasikmalaya in the 2022/2023 academic year in Indonesian language subjects with reference to digital literacy competencies. These competencies include: 1) Internet searching; 2) Hypertextual Navigatuon; 3) Content Evaluation; and 4) Knowledge Assembly. This research uses a qualitative approach with analytical descriptive method. The population of this study were students in grades X and XI of SMKS NU Tasikmalaya in the 2022/2023 academic year totaling 202 people, while the sample amounted to 16 people. The sampling technique used purposive technique by considering the main criteria, namely the facilities owned by students. The instrument used is a questionnaire using googleform and interviews via WhatsApp. The results showed that students in grades X and XI of SMKS NU Tasikmalaya had mastered all four digital literacy competencies, namely 1) internet searching with a good category; 2) hypertextual navigation with a good category; 3) information content evaluation; and 4) knowledge assembly with a good category. Apart from that, they still need guidance and direction regarding the credibility of the information and material they get. Based on this, it can be concluded that students in grades X and XI of SMKS NU Tasikmalaya in the 2022/2023 academic year have mastered all indicators of digital literacy competence in Indonesian language subjects.